Evaluating Test Strategies and Frameworks for High-Risk Separation Projects - Subash Lekshmi Velayudhan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article examines the critical aspects of test strategies and frameworks essential for high-risk IT separation projects. The article explores the complexities of separating deeply integrated enterprise systems while maintaining data integrity and business continuity. Through analysis of various case studies, including Oracle ERP and Workday implementations, the article presents a structured approach to testing methodologies, risk mitigation strategies, and quality assurance frameworks. The article addresses the challenges of managing multiple architectural layers, integration points, and organizational dependencies while providing best practices for successful separation initiatives. By examining both technical and organizational dimensions, this article offers valuable insights into effective testing strategies that ensure successful system separation while maintaining operational stability.
Keywords: Enterprise Architecture; Project Management; Risk Assessment; System Integration; Testing Frameworks